The forces of revenue recognition standard changes in a telecommunication company: A qualitative approach - Fauzi, Syazwani Izzati Mohd; Ali, Mazurina Mohd; Ghani, Erlane K (Journal of Ecohumanism, 2024)
Revenue recognition is one of the crucial key performance indicators for each organisation. The forces of the revenue recognition standard change may cause different experiences for organisations in many ways. Currently, the revenue recognition implementation method is different from what it was in the past. As a result, an organisation that goes through changes may have different experiences and approach problems differently. Organisational change may be triggered by external factors, such as government policies that specifically target a certain sector. Moreover, alterations in the criteria and protocols of regulatory entities might potentially initiate organisational change, in line with the coercive isomorphism of institutional theory. The objective of this study was to enhance comprehension of the forces influencing changes in revenue recognition standards within a telecommunications company by conducting an explanatory case study on a Malaysian telecommunications company. The semi-structured interviews were conducted to get better and more in-depth information on how the company handled the situation. This study found that external factors and regulatory regulations may significantly influence only a small part of an organisation, leading to changes in its operational structure and activities. These changes aim to improve performance, strengthen organisational stability, and promote improved financial reporting. The focus on the telecommunications industry may add to the body of knowledge concerning complex product-based industries. This study provides a foundation for further research into how such industries navigate regulatory changes and adapt their practices accordingly.